Estudo das propriedades estruturais e da dinâmica de nucleação do Óxido de Cobre nanoestruturado produzido por mecano-síntese - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
Using a sample of metallic copper Cu2O, was produced by mechanical alloying. The evolution of the structural properties of the sample was studied by x-ray diffraction (XRD), by making one XRD measurement after every two hours of milling during twenty four hours, in a step by step process. The final sample was analyzed by micro-Raman spectroscopy ( ). The time evolution of the structural properties of the samples was observed by refining the XRD diffractograms using the Rietveld method. The Williamson-Hall method was used in order to obtain the values of the microstrain and the crystallite size for the phases present in the sample. The nucleation dynamics of the phase was studied and described by the method of Johnson-Mehl-Avrami. After some time, the sample continued oxidation, making the phase of cupric oxide (CuO ) to appear.
Keywords: Moagem; Nanomateriais; Nucleação; Raman; Raios-x; CIÊNCIAS EXATAS E DA TERRA: FÍSICA